Modelo de Propagación de Interiores Para la Facultad Tecnológica de la Universidad Distrital - Pedraza Martínez, Luis Fernando; Hernández Suárez, César Augusto; Salcedo Parra, Octavio José (Ingeniería, 2007)
This paper aims to design an experimental model of indoor propagation for wireless in the Faculty of Technology of the Distrital University. Measurements of signal in the 850 MHz band were obtained with the cell phone ALCATEL OT - C717A and software CATCHER. This software allows measuring the power of receiving of the signal emitted by one of the base stations belonging to the network of Comcel, in addition to the radio channels used by the network to communicate with the cell. The result of this research is a model of propagation with a margin of error of less than 10% for the signal Comcel in the Faculty of Technology of the Distrital University.